Translation of Chinese version of the measure of audiologic rehabilitation self-efficacy for hearing aids and the self-efficacy among hearing aid users in China: Application of the questionnaire - Jiamei Chen; Ying Shen; Quanran Lin; Yanmei Feng; Hui Li (PLoS ONE, 2025)
Objectives To evaluate reliability and validity of the Chinese version of the Measure of Audiologic Rehabilitation Self-Efficacy for Hearing Aids (C-MARS-HA) and to analyze self-efficacy of Chinese hearing aid users. Design The Brislin translation model was strictly adopted to modify the C-MARS-HA. Participants included 134 hearing aid users aged 20–98. Hearing aid users were surveyed through questionnaire interviews regarding self-efficacy and overall satisfaction with hearing aids. Reliability and validity of the questionnaires were analyzed. Descriptive statistical and correlation analyses were conducted on the total score and four factors of the C-MARS-HA and overall satisfaction. Results In reliability analysis, Cronbach’ s α, Spearman-Brown, and Guttman split-half coefficients of the overall and four factors were all greater than 0.6, indicating that C-MARS-HA has acceptable reliability. In validity analysis, C-MARS-HA consisted of 24 items across 4 factors (basic handling, aided listening, adjustment and advanced handling) and had acceptable content validity. Exploratory factor analysis yielded with a four-factor solution, explaining more than 40% of the total variance and the loading coefficient for each of the 24 items was above 0.4, indicating that C-MARS-HA had good construct validity. Average scores for basic handling and adjustment were at least 80%, whereas average scores for aided listening, advanced handling, and total scores were less than 80%. A total of 65.67% of users had an overall satisfaction rate of 80%. A significant positive correlation (p < 0.001) was found between the total score of the questionnaire, the scores of the four factors, and overall satisfaction. Conclusions The reliability and validity of the C-MARS-HA is acceptable. This questionnaire can be used for clinical evaluation of self-efficacy among Chinese hearing aid users.